2024
DOI: 10.3390/toxics12020112
|View full text |Cite
|
Sign up to set email alerts
|

Human Health Risk Assessment from Mercury-Contaminated Soil and Water in Abu Hamad Mining Market, Sudan

Ahmed Elwaleed,
HuiHo Jeong,
Ali H. Abdelbagi
et al.

Abstract: Artisanal and small-scale gold mining (ASGM) poses a significant global threat due to mercury emissions and resulting health hazards. This study focuses on assessing these risks in the Abu Hamad ASGM community in Sudan. Utilizing the Mercury Analyzer 3000 (NIC), analyses of twelve soil samples (including one tailings sample) and seven water samples revealed the highest concentrations near amalgam burning locations: 34.8 mg/kg in soil (S06) and 3.26 µg/L in water (W03). Concentrations decrease with distance, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 52 publications
1
4
1
Order By: Relevance
“…Interestingly, this concentration contains nearly 50% of the lower end of the range of mercury concentrations found in the tailings in the current study (5.01 mg/kg). Another study in the Abu Hamad Mining Market [29] exhibited higher mercury concentrations in tailings samples, measuring 19.0 mg/kg, which is relatively higher than the concentration found in this study. This difference may be attributed to the nature of the tailings in the present study, which primarily consist of reprocessed amalgamation tailings.…”
Section: Mercury Concentration In Soil and Tailingscontrasting
confidence: 87%
See 4 more Smart Citations
“…Interestingly, this concentration contains nearly 50% of the lower end of the range of mercury concentrations found in the tailings in the current study (5.01 mg/kg). Another study in the Abu Hamad Mining Market [29] exhibited higher mercury concentrations in tailings samples, measuring 19.0 mg/kg, which is relatively higher than the concentration found in this study. This difference may be attributed to the nature of the tailings in the present study, which primarily consist of reprocessed amalgamation tailings.…”
Section: Mercury Concentration In Soil and Tailingscontrasting
confidence: 87%
“…To contextualize the results within the ASGM context in Sudan, a study in the Abu Hamad ASGM center revealed that all individuals in the ASGM center are at risk, primarily from the ingestion and inhalation of mercury vapors [29], which is consistent with the findings of this study regarding the inhalation of mercury vapors. Water samples collected from ASGM processing centers posed significant human health risks, especially for children, even though they are not allowed to be present in those areas [29]. However, individuals in ASGM centers are directly or indirectly involved in ASGM activities.…”
Section: Health Risk Assessmentsupporting
confidence: 81%
See 3 more Smart Citations